Families, Status and Dynasties : 1600-2000 - Jallinoja, Riitta (Palgrave Macmillan Studies in Family and Intimate Life, 2017)
This book takes a novel approach to family, exploring in detail how status is inherited and maintained within families; the process of upward social mobility; and how the roots of social decline start within families. The author also examines how rigidly status equivalence determines choice of spouse. Exceptionally extensive in its coverage, the book ranges from the seventeenth century to the present day, across a large range of European countries and part of the United States, and across several class groups, including royalty, nobility and entrepreneurial dynasties, as well as families of professionals, artists and those in lower ranks. The book also discusses the viability of the central sociological concepts of class and status. The book will be of interest to scholars and students in the areas of family sociology, history, social equality and inequality and class and elitism research.